Model SAVI terhadap Hasil Belajar dan Motivasi Belajar Siswa Pembelajaran Pendidikan Agama Islam di SMPIT Darel Iman - Mufti, Zulfi Aulia; Khadijah, Khadijah; Zulmuqim, Zulmuqim; Eliza, Rivdya; Kenedi, Gusril (Institut Agama Islam Sumatera Barat, 2024)
This research aims to determine the application of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model to learning outcomes and learning motivation for Islamic Religious Education in class VII SMPIT Dar El Iman. This research is experimental. The research design uses a Quasi-Experimental Design with a Posttest Only Control Design research design. The population in this study was class VII students at SMPIT Dar El Iman for the 2021/2022 academic year, totaling 62 students. Sampling uses saturated samples. Two classes are research subjects, namely class VII Makkah as the experimental class and class VII Medina as the control class. Based on the results of hypothesis testing using the manual t-test method, the data value = 5.8 > the value = 1.679. So it can be concluded that it was rejected and accepted. The number of test participants in the experimental class was 31 people with an average score of 89 and test participants from the control class were 31 with an average of 72. This means